APPARATUS AND METHODICAL COMPLEX FOR DETERMINATION OF OIL-GAS RESERVOIRS PARAMETERS WHILE DRILLING HORIZONTAL WELLS - Bondarenko, M.; Кulyk, V.; Yevstakhevych, Z.; Danyliv, S.; Zinenko, V.; Los, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper is devoted to the basic principles of the trend of logging, namely logging while drilling (LWD), which is new for Ukraine. The LWD technology has a number of advantages over other logging types, in particular, in supplementary exploration and production of hydrocarbons in fields that are in longterm development. In this case, the drilling of horizontal wells, which by productivity is much higher than the vertical ones, is important. For the investigations of horizontal wells, we proposed a universal compact radioactive logging tool with small diameter, which is placed in entire drill collar just before drilling. The combined radioactive logging tool LWD-KПРK-48 (48 mm in diameter) contains dual-spacing modules of neutron logging, neutron-gamma logging, density logging, as well as separately placed gamma-logging unit. Calibration works with the developed combined tool were carried out on physical models of reservoirs in the presence of drill collars and corresponding calibration dependences on porosity and density were obtained. They, together with the developed methods and other data, allow us to determine an extended set of petrophysical parameters, namely, the porosity of water-, oil- and gas-saturated reservoirs, the identification parameters of fluid: water – oil and water – gas, oil-, gas- and water saturation, volume content of oil and gas, etc. Test of a logging tool LWD-KПРK-48 when drilling a horizontal well in an oil-bearing bed showed high informativity and efficiency of product. The created apparatus and methodical complex for the investigation of horizontal oil and gas wells while drilling has several advantages over known analogues, in particular, is universal, convenient, more available to mining and well logging oil and gas companies.
Keywords: logging while drilling; horizontal wells; oil and gas reservoirs; combined radioactive logging tool; interpretating-methodical support; petrophysical parameters